Model Perancangan Aplikasi Pesantren Matic Pada Forum Pondok Pesantren Jawa Barat - Edi Komarudin; Ramadhan Syaeful Bahri; Dyan Fachri Maulana; Ananda Rizky Maulana (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2019)
Pesantren Matic application is a website-based application that provides features for recording financial statements and as a tool for business development for the West Java Boarding School Forum. With a website-based application, FPP West Java can start a business in the form of ustadz training and certification, boarding school management governance training and training in recording the pesantren's financial statements. The target of this program is Islamic boarding schools in Indonesia and especially West Java. The Business Model Canvas used explains that: key partners (Ministry of Religion of West Java Province, Indonesian Ulama Council, Islamic Boarding Schools), key activities (Financial Recording, Islamic Boarding School Training, Ustadz training & certification), key resource (West Java Boarding School Forum), value proposition (Integrated Ministry of Religion, Indonesian Ulema Council), Customer Relationship (Advertising (promos and subscriptions)), Channels (Website, Social Media, Advertising), Customer Segments (Pondok Pesantren, Ustadz), Cost Structure (Domain and Hosting Registration Fees) ), Revenue Streams (Financial Records, Islamic Boarding School Training, Ustadz training & certification).